A PHENOMENOLOGICAL ANALYSIS OF LENA HALOWAY’S EXPERIENCE IN LAUREN OLIVER’S DELIRIUM NOVEL - Pitaloka, Epifani Putri; Natsir, M.; Valiantien, Nita Maya (Fakultas Ilmu Budaya Universitas Mulawarman, 2022)
ABSTRACTThis research reports a phenomenological analysis in Lena Haloway’s experience following the traumatic events. Phenomenology describes the meaning of experience as the essence of a phenomenon, and explores the perspective to learn from the experience of others. It gives reflection to the issues important to the research. Delirium novel portrays the character of Lena Haloway who has experienced tremendous amount of loss in her life and she also has experienced the struggle living under the totalitarian government that seems to dictate her decisions. That traumatic experience affects her perspective of the world she lives in. This research uses qualitative-descriptive method and purposes to examine the phenomenological concepts of Lena Haloway’s experiences and how they are affects her perspective represents in Delirium novel by using Husserl’s Phenomenology and Heidegger’s Hermeneutic theories. The result reveals that Lena experienced all five phenomenological concepts of experience; those are intentionality, noema, noesis, intersubjectivity, and intuition. It also shows that those experiences affect her perspective. All the results represent through Lena’s narration, actions, and feelings as the first person narrator.Key words: phenomenology, hermeneutic, experience, affect, perspective ABSTRAKPenelitian ini melaporkan analisis fenomenologis dalam pengalaman Lena Haloway setelah mengalami peristiwa traumatis. Fenomenologi menggambarkan makna pengalaman sebagai esensi dari suatu fenomena dan menggali perspektif untuk belajar dari pengalaman orang lain. Ini memberikan gambaran pada masalah penting untuk penelitian ini. Novel Delirium menggambarkan karakter bernama Lena Haloway yang mengalami banyak kehilangan dalam hidupnya dan ia juga mengalami sulitnya hidup di bawah pemerintahan totaliter yang mengatur keputusannya. Pengalaman traumatis tersebut memengaruhi perspektifnya terhadap dunia yang ia tinggali. Penelitian ini menggunakan metode kualitatif-deskriptif dan bertujuan untuk mengkaji konsep fenomenologi dalam pengalaman Lena Haloway dan bagaimana pengalaman tersebut memengaruhi perspektifnya tentang hidup yang tergambar dalam novel Delirium dengan menggunakan teori fenomenologi oleh Husserl dan teori hermeneutika oleh Heidegger. Hasil mengungkapkan bahwa Lena mengalami kelima konsep fenomenologi, yaitu kesengajaan, noema, noesis, intersubyektivitas, dan intuisi. Hal tersebut juga menunjukan bahwa pengalaman tersebut telah memengaruhi perspektifnya. Data dikumpulkan melalui narasi, tindakan, dan perasaan Lena dalam sudut pandang orang pertama.Kata kunci: fenomenologi, hermeneutika, pengalaman, pengaruh, perspektif